2018
DOI: 10.1590/1413-81232018231.14412015
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health in the Family Health Strategy: analysis of articles published in the period 2004-2014

Abstract: This study aimed to conduct an integrative review of scientific literature on the topic of Oral Health in the Family Health Strategy in the period 2004-2014. Articles published in national and international journals (n = 141) were consulted and selected from the electronic Library the Scientific Electronic Library Online (SciELO) and from electronic databases PubMed, Lilacs, BBO and Cochrane. The implementation process of oral health teams in the Family Health Strategy was the most frequent thematic variable (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
1
0
0
1
Order By: Relevance
“…The results of the research showed that all the pregnant women reported lack of knowledge about how to prevent PG and maintain oral health during the gestational period. Similar results were observed in other studies that reported on the fact that pregnant women using the public service received little guidance on oral health, and consequently did not value dental follow-up during this period [13,14,15,16].…”
Section: Discussionsupporting
confidence: 89%
“…The results of the research showed that all the pregnant women reported lack of knowledge about how to prevent PG and maintain oral health during the gestational period. Similar results were observed in other studies that reported on the fact that pregnant women using the public service received little guidance on oral health, and consequently did not value dental follow-up during this period [13,14,15,16].…”
Section: Discussionsupporting
confidence: 89%
“…Carneiro Neto et al (2014) destacam que o cuidado humanizado demanda um modelo de formação para além da clínica tradicional. Além da preparação técnica do estudante, é fundamental que o oferecimento de cuidados envolva o reconhecimento das necessidades psicossociais dos usuários do serviço, bem como, o planejamento e implementação de estratégias que auxiliem o paciente no aprendizado de ações de autocuidado, colaborando para sua autonomia, recuperação ou manutenção de sua saúde, bem como, o bem-estar de indivíduos, famílias e comunidades (Mota et al 2012;Dalazen et al, 2018).…”
Section: Introductionunclassified